Peningkatan Karakter Kemandirian dan Tanggung Jawab dengan Menggunakan Model Asanti Emotan pada Anak Kelompok B TK Dharma Wanita Kanigoro I - Wijaya, Ika; Parji, Parji; Hanif, Muhammad (Universitas PGRI Madiun, 2024)
The aim of this study For describe and analyze enhancement character independence and responsibility answer as well as increase character independence and responsibility answer with using the asanti model emoting at children group B Kindergarten Dharma Wanita Kanigoro I. This research uses approach qualitative with type of PTK implemented in two cycles , each cycle consists on planning , implementation action , observation , and reflection . Implementation time October 2023 to April 2024. Data collection techniques with use observations and documents . Data analysis via data reduction , data presentation , data retrieval and verification.Results research in cycle I character independence was 33% in cycle II increased to 83%. Whereas not quite enough the answer in cycle I was 42% in cycle II to 87%. With thereby achievements completeness Already exceed indicator performance reaches 80%. Model Asanti Emotan capable increase character independence and responsibility answer the child Group B Kindergarten Dharma Wanita Kanigoro I.